PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION - V. Mardi Widyadmono (Jurnal Manajemen Indonesia, 2015)
This study assesses the influence of job satisfaction and organizational commitment on Turnover Intention. Futhermore, the study identify the mediation role of organizational commitment in the relationship between job satifaction and Turnover Intention. The participants of the study are 98 employees working in private companies operated in Yogyakarta, (36 men and 62 women). Respondents complete questionnaire containing questions on job satisfaction variable, questions on organizational commitment and questions on Turnover Intention. The statistics tools applied are regression analysis to assess the relation between variables and Sobel test to measure the mediation role of organizational commitment. The results of the investigation revealed that job satisfication and organizational commitment influence negatively and significantly Turnover Intention. The higher the job satisfication and the organizational commitment of employees lead to the lower Turnover Intention. The organizational commitment does not play mediation role in the relationship between job satisfication and Turnover Intention